Low Genetic Diversity of the Endangered Franciscana (Pontoporia blainvillei) in Its Northernmost, Isolated Population (FMAIa, Espírito Santo, Brazil) - de Oliveira, Vanessa K. M.; Faria, Drienne M.; Cunha, Haydée A.; dos Santos, Teresa E. C.; Colosio, Adriana C.; Barbosa, Lupércio A.; Freire, Mylla Carla C.; Farro, Ana Paula C. (Frontiers in Marine Science, 2020)
The franciscana, Pontoporia blainvillei, is the most endangered small cetacean in the Southwestern Atlantic Ocean, occurring from Itaúnas, Espírito Santo, Brazil to Chubut province, Argentina. This area is divided into four Franciscana Management Areas (FMA). The northern portion of this species distribution is not continuous and a previous genetic study using mitochondrial DNA (mtDNA) separated it into FMAIa (Espírito Santo state) and FMAIb (North of Rio de Janeiro state). In order to increase the information about this population we expanded the sample number and evaluated mitochondrial and nuclear DNA diversity. Samples of 68 franciscanas found stranded on beaches from 2005 to 2020 were analyzed. Analyses included 350 bp of the mtDNA control region (D-loop) and 12 microsatellite loci. We identified three control region haplotypes in FMAIa, two of them not previously observed in this population, one being a new haplotype. Haplotype and nucleotide diversities were 0.0408 and 0.00012 respectively, the lowest reported for all FMAs analyzed until now. The Neutrality tests were not significant and Mismatch Distribution analysis did not reject the hypothesis of population expansion. One of the microsatellite loci was monomorphic, and for the other loci, two to nine alleles were identified, with expected heterozygosities ranging from 0.306 to 0.801. No substructure was revealed and effective population size (Ne) was estimated in 117.9 individuals. Even with an increased sample size, the high mitochondrial genetic homogeneity suggested for the population in a previous study was confirmed. Among six loci previously analyzed in other franciscana populations, five showed the lowest observed heterozigosities for the Espírito Santo population. The novel microsatellite data also showed low genetic diversity and could not reject the hypothesis of a single, panmitic population along the coast of Espírito Santo. This species has been intensively impacted in the last years by incidental capture during fishing activities and habitat degradation, caused by pollution, coastal development and environmental disasters in FMAIa. Considering that this population is small, isolated, and with low levels of genetic diversity, we reinforce the necessity of different conservation actions, focusing mainly on the reduction of bycatch of this species in the region.